The Road to Terrace Bank: Land Capitalization, Public Space, and the Redpath Family Home, 1837-1861 - Macleod, Roderick (Journal of the Canadian Historical Association / Revue de la Société historique du Canada)

(untitled) (The Canadian Historical Association / La Société historique du Canada, 2003)
AbstractThe efforts of nineteenth-century Montreal land developer John Redpath to subdivide his country estate into residential lots for the city's rising middle class were marked by a shrewd sense of marketing and a keen understanding of the political climate – but they were also strongly determined by the Redpath family's need for status and comfort. Both qualities were provided by Terrace Bank, the house at the centre of the estate, and both would only increase with the creation of a middle-class suburb around it on the slopes of Mount Royal. As a result, the Redpath family home, and the additional homes built nearby for members of the extended Redpath family, influenced all stages of the planning and subdivision process, which met with great success over the course of the 1840s. In its use of personal correspondence, notarial documents, plans, the census, and cemetery records, this paper brings together elements of city planning, political and social history, and family history in order to provide a nuanced picture of how the nineteenth-century built environment was shaped and how we should read pubic space.